Election results and opportunistic policies : a new test of the rational political business cycle model - Aidt, Toke S. (2011)
The literature on the rational PBC suggests that politicians systematically manipulate economic and fiscal conditions before elections to increase their chances of reelection. Most tests of this theory look for evidence of pre-election distortions in fiscal policy. We propose a new test that explores the two-way interaction between the magnitude of the opportunistic distortion and the margin of victory. The test is implemented using a large panel of Portuguese municipalities. The results show that opportunism leads to a larger winmargin for the incumbent and that incumbents behave more opportunistically when their win-margin is small. These results are consistent with the theoretical model.